Generation Z Investment Decision: An Analysis Using Behavioral Factors - Iqbal Fadhiil; Putri Fariska (Dinasti Publisher, 2024)
Investment has gotten more known and popular since a few years back, particularly during the pandemic. The growth itself was majorly contributed by people within the age group of Generation Z. One of the most contributing factors of their participation is their fear of missing out, especially with the exposure of social media investment content. Their behavioral biases oftentimes result in loss instead of return, due to the unwise investment decisions. This research investigates the behavioral bias within the investment decision-making of Generation Z in the area of Greater Bandung, with the sample of 489 individuals. The collected data from the sample through questionnaires analyzed using SPSS software with Multiple Linear Regression method. The results show that trait anger does not partially influence investment decision significantly, while trait anxiety, overconfidence, herding behavior, and self-monitoring partially influence investment decision significantly. All the independent variables simultaneously influence investment decision.